The role of nature in contemporary literature: an interdisciplinary dialogue - Davi Silva Gonçalves; Eliana de Souza Ávila (INTERthesis)
The purpose of this paper is to analyse how the dialogue between literature and the environment might actively interfere in society’s behaviour concerning the ecological problems in vogue today. In this sense, the bibliographical research is structured on hypotheses which problematise dominant systems in the contemporary intellectual, social, and economic spheres, highlighting ecocriticism as a pivotal theoretical perspective for the relation between subject and surrounding space to be rethought. Bringing the Amazon as to materially illustrate the importance for such theme to be discussed, the article proposes alternatives external to the ones posed by developmentalist policies, whose worries generally regard material profit reached through the alienation of the population so convinced of the benefits of such process. Such process, thus, takes place through the institutionalisation of Amerindian’s culture, their insertion in the capitalist world, and, especially, the obliteration of Amazonian environment and the extinction of native species. Going to the opposite direction, literature might be utilised as a counter-hegemonic tool able to allow readers to consider other definitions for their relation with the environment.